Educação popular e subjetividade na feira agroecológica - Silva, Nelsânia Batista da (2006)
This research has got as objective to analyze the educational dimension and subjective features presents at the Agroecological Fair. The fair takes place at Universidade Federal da Paraíba (UFPB), Campus I, in João Pessoa, being managed by worker men and women of agrarian reform settling down areas in Paraíba meadow. The methodology used was defined by qualitative research practice, making use of participative observation techniques, of half-structured interviews, of field notes, photograthic record, meetings and workshops participation, visits to workers houses and follow-up activities during the fair. A methodology that observed 3 movements: the first, a synthesis, expressed by configuration theoretical elements of reality features and its explanation, the second movement, and analysis, interpreted by fair characteristics search, having as instruments the early theoretical elements, and the third movement, a new synthesis, dive to early movements, standing out fair experience subjectivity features. The research detach educational-popular features of this experience and shows subjectivity elements that give maintenance to exerting relations, as well as suggests the fair as life alternative, differentiated from society dominant developing logics maintenance, by popular economy with solidarity and orientated by relations human principles, as the solitary, equality and cooperation.